A Study on Automatic Feedback Control by Image Processing for Mixing Solutions in a Microfluidic Device - Heena T Shaikh; Kazi Kutubuddin Sayyad Liyakat (International Journal of Advanced Control and System Engineering, 2025)
Precise and rapid mixing of chemical and biological reagents is a critical yet challenging aspect of microfluidic systems, often limited by laminar flow conditions and the need for manual or pre- programmed interventions. Existing mixing strategies frequently lack real-time adaptability and closed-loop control, hindering reproducibility and the execution of complex reaction protocols. This work presents an innovative automatic feedback control system utilizing the study on real- time image processing to dynamically optimize the mixing of solutions within a microfluidic device. The design and implementation of a novel automatic feedback control system that uses real-time image processing to dynamically improve solution mixing within a microfluidic device is presented in this study in order to overcome these constraints. The device combines a microfluidic chip with programmable reagent inlets with a high-speed imaging setup and specially designed image processing software. Through the use of fluorescent markers to continuously monitor local concentration gradients, the image processing system may provide real-time feedback to dynamically modify the flow rates of individual inlets. The precise manipulation of reagent concentrations and flow patterns is made possible by this closed-loop feedback mechanism, which guarantees that mixing is actively regulated rather than passively induced. The system integrates a high-speed camera, custom image analysis software, and a microfluidic chip with controllable reagent inlets. By continuously monitoring the local concentration gradient via fluorescent markers, the image processing algorithm provides instantaneous feedback to modulate flow rates of individual inlets. The system's experimental evaluation shows a significant improvement in homogeneity and mixing efficiency under a variety of operating situations. The system maintains performance even when input flow rates or reagent concentrations fluctuate dynamically, reliably achieves the correct mixing ratios, and shortens the time needed to accomplish uniform reagent distribution. In addition to increasing efficiency, the method improves reproducibility, which lowers variability brought on by manual operation and permits consistent results across multiple experiments. This closed-loop approach demonstrated significantly enhanced mixing efficiency and homogeneity, robustly achieving desired mixing ratios and reducing the time to reach uniform distribution even under varying input conditions. The developed system offers a robust, autonomous, and highly reproducible platform for precise microfluidic mixing, paving the way for advanced chemical synthesis, biological assays, and diagnostic applications requiring dynamic control over reaction environments.
Keywords: Automatic feedback control; Closed loop approach; Microfluidic Device; image processing